2016
DOI: 10.2215/cjn.02560315
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission in the Nephrotic Syndrome Study Network

Abstract: Background and objectives This analysis from the Nephrotic Syndrome Study Network (NEPTUNE) assessed the phenotypic and pathology characteristics of proteinuric patients undergoing kidney biopsy and defined the frequency and factors associated with complete proteinuria remission (CRever).Design, setting, participants, & measurements We enrolled adults and children with proteinuria $0.5 g/d at the time of first clinically indicated renal biopsy at 21 sites in North America from April 2010 to June 2014 into a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…NEPTUNE is part of the National Institutes of Health (NIH) Rare Disease Clinical Research Network (RDCRN). The study design and cohort baseline description are published (Gadegbeku et al, 2013; Gipson et al, 2016). NEPTUNE was approved by collaborating center Institutional Review Boards, and subjects or guardians provided consent to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NEPTUNE is part of the National Institutes of Health (NIH) Rare Disease Clinical Research Network (RDCRN). The study design and cohort baseline description are published (Gadegbeku et al, 2013; Gipson et al, 2016). NEPTUNE was approved by collaborating center Institutional Review Boards, and subjects or guardians provided consent to participate.…”
Section: Methodsmentioning
confidence: 99%
“…eGFR (mL/min/1.73m 2 ) was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula for participants ≥ 18 years old and the modified CKiD-Schwartz formula for children < 18 years old. CKD progression was evaluated with a composite of 40% decline in eGFR from baseline or end-stage renal disease (ESRD) (Mariani et al, 2017; Levey et al, 2014), defined as the initiation of dialysis, kidney transplant, or eGFR < 15 mL/min/1.73 m 2 on two measurements (Gipson et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Full details of the study design and baseline description of the cohort have been published elsewhere. 28, 29 Eligibility criteria include: individuals of any age scheduled for a clinically-indicated renal biopsy with proteinuria ≥ 500 mg/day from a 24-hour or random (protein to creatinine ratio (UPCR) > 0.5 g/g) urine sample. Patients with sub-nephrotic proteinuria were included to capture the broad spectrum of clinical presentations.…”
Section: Methodsmentioning
confidence: 99%
“…17 (Table 1) FSGS now accounts for 20 to 40% of all biopsy-proven glomerular diseases in adults. 38 However, the previous studies have important limitations. First, the majority of the studies reported trends in relative disease frequencies among biopsied patients rather than true population-based incidence rates of FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…Another important limitation in the previous studies is the approach of reporting FSGS as a single disease entity. 28 We now know that FSGS is a histological pattern of injury that characterizes a broad spectrum of diseases with different pathophysiologies. Primary FSGS is presumed to be due to a circulating permeability factor diffusely toxic to podocytes, which may respond to immunosuppressive treatment.…”
Section: Introductionmentioning
confidence: 99%